2007
DOI: 10.1111/j.1365-2222.2007.02905.x
|View full text |Cite
|
Sign up to set email alerts
|

Mould‐specific immunoglobulin antibodies quantified by flow cytometry reflect mould exposure in Norwegian children

Abstract: SummaryBackground Studies from many countries have shown an association between dampness in buildings and airway symptoms. Little is known about the role of mould-specific IgG antibodies in this context. Objective To examine the IgG antibody response to mould applying a new flow cytometric assay, compare the results with the standardized ImmunoCap s method, and evaluate the association of IgG to IgE antibodies, dampness in buildings, and airway symptoms like wheeze and asthma. Methods A population of 3713 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It seems plausible to think that mold exposure induces an inflammatory reaction, but it could also be the other way round, in that genetically susceptible individuals with a higher pro-inflammatory profile due to their evolutionary past, will respond to lower threshold of mold and dampness exposure. Like women being generally more prone to most autoimmune diseases as a trade-off to a higher inflammatory potential to combat infectious disease, women do not only suffer more often form sick building syndrome but also display higher mold-specific IgG-antibodies than men (86, 87). If the hypothesis is true that MHSD is a trade-off to avoid or defend potential invasive or dangerous pathogens, these individuals should have a lower probability of invasive fungal disease.…”
Section: Resultsmentioning
confidence: 99%
“…It seems plausible to think that mold exposure induces an inflammatory reaction, but it could also be the other way round, in that genetically susceptible individuals with a higher pro-inflammatory profile due to their evolutionary past, will respond to lower threshold of mold and dampness exposure. Like women being generally more prone to most autoimmune diseases as a trade-off to a higher inflammatory potential to combat infectious disease, women do not only suffer more often form sick building syndrome but also display higher mold-specific IgG-antibodies than men (86, 87). If the hypothesis is true that MHSD is a trade-off to avoid or defend potential invasive or dangerous pathogens, these individuals should have a lower probability of invasive fungal disease.…”
Section: Resultsmentioning
confidence: 99%
“…These differing results may be attributed to several factors, including use of different means of measuring mold and dampness. For example, Jaakkola et al [21] and Rydjord et al [22] based their measurement on self-reported exposure data, whereas Hyvärinen et al [23] used a standardized home inspection kit to determine the presence of mold in homes of newly diagnosed asthma patients. In other studies, mold exposure quantification was performed or levels of visible mold were measured.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative measures of mold and water damage are the most commonly used, as these are the easiest to obtain and can rely on questionnaires. Rydjord et al 5 found self-reported visible signs of mold or moisture at home during the child’s first year of life were a significant risk factor for ever having wheeze or asthma. A longitudinal study by Jaakkola et al 6 focused on the effects of parent-reported exposure to molds in dwellings on the development of asthma in childhood.…”
Section: Introductionmentioning
confidence: 99%